Enhanced Therapeutic Efficacy of Combining Losartan and Chemo-Immunotherapy for Triple Negative Breast Cancer - Zhao, Qing; He, Xuexin; Qin, Xiyi; Liu, Yu; Jiang, Han; Wang, Jing; Wu, Shuang; Zhou, Rui; Yu, Congcong; Liu, Suling; Zhang, Hong; Tian, Mei (Frontiers in Immunology, 2022)
Triple-negative breast cancer (TNBC) is a particularly aggressive subtype of breast cancer, which is relatively resistant to anti-programmed cell death-1 (α-PD1) therapy, characterized as non-immunogenic, dense stroma and accumulation of M2 tumor-associated macrophages (TAMs). Despite progress in strategies to deplete extracellular matrix (ECM) and enhance tumor-cell immunogenicity, the combinatorial anti-cancer effects with α-PD1 need to be explored. Here, we applied doxorubicin hydrochloride liposome (Dox-L) as immunogenic cell death (ICD)-inducing nano-chemotherapy and used losartan as stroma-depleting agent to improve α-PD1 efficacy (Losartan + Dox-L + α-PD1). The results showed that losartan could cause ECM reduction, facilitating enhanced delivery of Dox-L and further dendritic cell (DC) maturation. Additionally, losartan could also alleviate hypoxia for TNBC, thus reprogramming pro-cancer M2 TAMs to anti-cancer M1 TAMs, successfully overcoming immune-suppressive microenvironment. These modifications led to a significant increase in T cells’ infiltration and augmented anti-tumor immunity as exemplified by the notable reduction in tumor size and lung metastases. In summary, our findings support that combined treatment of losartan with Dox-L normalizes immunological-cold microenvironment, improves immunostimulation and optimizes the efficacy of TNBC immunotherapy. A novel combinational strategy with FDA-approved compounds proposed by the study may potentially be useful in TNBC clinical treatment.